1989
DOI: 10.1128/mcb.9.12.5676
|View full text |Cite
|
Sign up to set email alerts
|

Expression of dicistronic transcriptional units in transgenic tobacco.

Abstract: We investigated whether the two cistrons of a dicistronic mRNA can be translated in plants to yield both gene products. The coding sequences of various reporter genes were combined in dicistronic units, and their expression was analyzed in stably transformed tobacco plants at the RNA and protein levels. The presence of an upstream cistron resulted in all cases in a drastically reduced expression of the downstream cistron. The translational efficiency of the gene located downstream in the dicistronic units was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Therefore, we assume that this variation is intrinsic to the composition of the chimeric constructs and unrelated to PTGS. Addition of a coding sequence to a gene construct has also been shown to decrease signi®cantly the steady-state levels of transcript accumulation (Angenon et al 1989;Van Blokland et al 1994). Here, we show that each gus construct with sequence homology to the nptII transgene yields signi®cantly lower GUS activities in nptII-silenced HOlo1 and HOloA leaves than in non-silenced HOlo2 leaves (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assume that this variation is intrinsic to the composition of the chimeric constructs and unrelated to PTGS. Addition of a coding sequence to a gene construct has also been shown to decrease signi®cantly the steady-state levels of transcript accumulation (Angenon et al 1989;Van Blokland et al 1994). Here, we show that each gus construct with sequence homology to the nptII transgene yields signi®cantly lower GUS activities in nptII-silenced HOlo1 and HOloA leaves than in non-silenced HOlo2 leaves (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The translational efficiency of the downstream ORF in a dicistronic construct is only 0n3-2n5 % of that in a monocistronic construct (Kaufman et al, 1987) when artificially engineered transcription units consisting of several normal-sized cistrons are introduced into mammalian cells. In plants, Angenon et al (1989) reported that a value 500-fold lower was obtained with a dicistronic unit.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the plasmid sequences upstream of the LlHs construct are not necessary for LlHs transcription, although they are capable of modulating it (Fig. 9) (7,11,15,21,34,44,59). Like LlHs, the picornaviruses contain long 5' UTRs in which are found several AUG codons and short ORFs (34).…”
Section: Methodsmentioning
confidence: 99%